Inspiratory muscle training in children with neuromuscular disorders - Anri Human; Lieselotte Corten; Eleonora Lozano-Ray; Brenda M. Morrow (AOSIS, 2024)
Background: Progressive respiratory muscle weakness and ineffective cough contribute to morbidity and mortality in children with neuromuscular disorders (NMD). Inspiratory muscle training (IMT) aims to preserve or improve respiratory muscle strength and reduce respiratory morbidity. This study aimed to determine the safety and efficacy of IMT in children with NMD. Methods/design: A randomised cross-over study compared a 3-month intervention (IMT) with control periods (no IMT). Children diagnosed with NMD (5 years - 18 years) performed 30 breaths (at 30% of maximum inspiratory mouth pressure [Pimax]) with an electronic threshold device, twice daily. During the control period, participants did not perform any IMT. Discussion: Twenty three children (median [interquartile range IQR] age of 12.33 [10.03-14.17] years), mostly male (n = 20) and non-ambulant (n = 14) participated. No adverse events related to IMT were reported. No difference in median patient hospitalisation and respiratory tract infection (RTI) rates between non-training and intervention periods (p = 0.60; p = 0.21) was found. During IMT, Pimax and peak cough flow improved with a mean ± standard deviation (s.d.) of 14.57 ± 15.67 cmH2O and 32.27 ± 36.60 L/min, compared to 3.04 ± 11.93 cmH2O (p = 0.01) and −16.59 ± 48.29 L/min (p = 0.0005) during the non-training period. Similar to other studies, spirometry did not show a significant change. Conclusion: A 3-month IMT programme in children with NMD appears safe and well-tolerated, with significant improvement in respiratory muscle strength and cough efficacy. Clinical implications: Inspiratory muscle training could be considered a cost-effective adjunct to respiratory management in children with NMD. Trial Registration: Pan African Clinical Trial Registry, PACTR201506001171421, https://pactr.samrc.ac.za.